Exploring The Principals’ Visionary Leaderships’ Effect on School Organizational Culture and Teachers’ Affective Commitment - Widodo, Widodo; Chandrawaty, Chandrawaty (Technium Social Sciences Journal, 2021)
This study explores the effect of principals’ visionary leadership (PVL) on school organizational culture (SOC) and teachers’ affective commitment. A questionnaire collected data through the survey methods toward 455 teachers of the public elementary school in Indonesia spread across seven provinces (Jakarta, Banten, West Java, Central Java, Riau Island, NTT, East Kalimantan). Data analysis uses path analysis supported by descriptive statistics and correlational. The results show that PVL had a significant effect on affective commitment mediating by SOC. Thus, the teacher’s affective commitment can improve through PVL and SOC. This finding can discuss as a reference among practitioners and researchers to develop better models of teacher’s affective commitment in the future and various filed and contexts.